DAMPAK REVOLUSI SOSIAL TERHADAP KERAJAAN RAYA DI SIMALUNGUN TAHUN 1946 - Tiopan Purba; Bedriati Ibrahim; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Indonesia’s indepence in 1945 became a new history in this country. Independence is also the turning point in social dynamics, resulting in drastic social changes in society. Social change after the proclamation is what is often called the social revolution. Social revolution almost happened in every region in Indonesia. One of them is social revolution that occurred in Sumatra, especially in eastern Sumatra. As for the purpose of this study is 1) to find out the background of the social revolution in the Raya’s Kingdom of Simalungun in 1946, 2) to find out the process of the ongoing social revolution in the Raya’s Kingdom of Simalungun in 1946, 3) to find out the impact of social revolution in the Raya’s Kingdom of Simalungun in 1946. As for this study using qualitative methods and data obtained from the interviws added to the data obtained from books and archives. The result of this research is that the social revolution in Raya’s kingdom is a dark tragedy for the people of Raya and even the people of Simalungun which cannot be forgotten. The social revolution in the Raya’s kingdom was driven by major A.E Saragih Ras who gathered in the Range Wild Tiger organization. He also mobilized farmers and fisherman and young man in Simalungun to destroy Raya’s kingdom. Since the social revolution, the empire vanished.Key Words: Social Revolution, Independence, Raya’s kingdom, Simalungun